2018
DOI: 10.1111/cea.13124
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between rhinovirus‐induced acute asthma and asthma‐augmented influenza infection

Abstract: In children with respiratory symptoms and/or fever, RV but not IFV is associated with wheeze and an asthma-like presentation. In those with an asthma history, IFV causes more generalised and severe disease that may be better described as "asthma-augmented influenza" rather than an "asthma attack." Differences in the acute conditions caused by these viruses should be considered in the design of epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The microbial colonisation of the nasal cavity and nasopharynx in early life has been linked with wheeze episodes and progression to asthma, potentially mediated through resistance or susceptibility to acute respiratory infections during childhood 18-22 . Compared to cellular microbes, respiratory viruses are currently considered the most important drivers of asthma development, exacerbation and persistence [23][24][25][26][27] . Upper respiratory viruses, most importantly rhinoviruses (RV), are strongly implicated in the induction of airway hyperresponsiveness and airway remodelling 1,4, [28][29][30][31] . Impairment of innate immune responses in children with asthma results in defective pathogen recognition, impaired interferon release and suboptimal antiviral responses 32,33 , and drives the development of biased T2 inflammation 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…The microbial colonisation of the nasal cavity and nasopharynx in early life has been linked with wheeze episodes and progression to asthma, potentially mediated through resistance or susceptibility to acute respiratory infections during childhood 18-22 . Compared to cellular microbes, respiratory viruses are currently considered the most important drivers of asthma development, exacerbation and persistence [23][24][25][26][27] . Upper respiratory viruses, most importantly rhinoviruses (RV), are strongly implicated in the induction of airway hyperresponsiveness and airway remodelling 1,4, [28][29][30][31] . Impairment of innate immune responses in children with asthma results in defective pathogen recognition, impaired interferon release and suboptimal antiviral responses 32,33 , and drives the development of biased T2 inflammation 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we need greater clarity on the different immune responses in view of the rising prevalence of chronic diseases such as diabetes mellitus and asthma. Patients with these disorders are especially susceptible to severe influenza complications compared to healthy subjects [12]. Thus, the establishment of a baseline response against influenza infection of “healthy” tissue is beneficial to facilitate future comparative studies to better manage influenza in patients with co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Karayama tested how respiratory impedance relates to airway narrowing by imaging the asthmatic airways using quantitative computed tomography. 81 The authors found that while respiratory resistance was correlated with reduced airway calibre in adults with asthma, respiratory reactance was not. Notably, respiratory impedance provided a sensitive tool, given that altered airway structure in lower branching bronchi and impaired impedance were present in those asthmatics who had normal spirometry.…”
Section: Airway Narrowing In Asthmamentioning
confidence: 99%